Peran Komisi Pemilihan Umum Dan Pengawas Pemilu Untuk Pemilu Yang Demokratis - Suparman Marzuki (Fakultas Hukum Universitas Islam Indonesia, 2008)
To build a strong and reliable democratic institution, is a time consuming process which also requires a long patience. Accordingly, three pillars of General Election Commission (KPU), namely, structural independency, functional independency and personal independency, shall be consistently kept up and maintained.